Evaluation of the Clinical Efficacy and Complications of Duloxetine in Comparison to Solifenacin in the Treatment of Overactive Bladder Disease in Women: A Randomized Clinical Trial - Mirzaei, Mahboubeh; Daneshpajooh, Azar; Anvari, Seyed Omidreza; Dozchizadeh, Salar; Teimorian, Mohamad (Urology Journal, 2021)
Purpose: SNRIs (serotonin and norepinephrine reuptake inhibitors) like duloxetine are known to have role in the treatment of anxiety disorder and stress urinary incontinence. According to the correlation of anxiety disorder and overactive bladder, this study aimed to evaluate the clinical efficacy and complications of duloxetine (SNRI) as a medication in the treatment of overactive bladder in the female patients. We were interested to know the probable therapeutic effect and side effects of duloxetine in overactive bladder. Methods and Materials: In this single-blinded interventional randomized clinical trial, 60 female patients with idiopathic overactive bladder (hyperreflexia) referred to the urology clinic, were divided into two groups as pilots. The first group were treated by 10mg/daily solifenacin and the second group received 20mg/daily duloxetine. The patients were evaluated by the ICIQ-OAB Questionnaire before and after one-month follow-up period. The intervention primary outcomes were evaluated by the patient’s presentation of the frequency, nocturia, urgency, urge urinary incontinence and the drugs side effects as secondary outcomes were checked. Results: Sixty women with confirmed overactive bladder disease were evaluated. Solifenacin and duloxetine had the same effect on the treatment of overactive bladder (p value=0.148). The clinical symptoms were obviously relieved in both groups after treatment. Side effects were insignificantly more common in the solifenacin group (p value>0.05). However, the different frequency of blurred vision in the two groups was statistically significant (p value=0.04). The most common complication in solifenacin and duloxetine group was anxiety. Conclusion: The results showed that solifenacin and duloxetine improved overactive bladder symptoms. According to this evaluation, duloxetine can be a suitable alternative option for overactive bladder treatment, due to the acceptable therapeutic effect and side effects.